Manajemen Humas dalam Penguatan Karakter Peserta Didik melalui Kolaborasi Sekolah dan Orang Tua di Madrasah Aliyah 03 Al-Ma’arif: Public Relations Management in Strengthening Student Character Through Collaboration Between Schools and Parents at Madrasah Aliyah 03 Al-Ma'arif - Abdul Majid; Ahmad Irsyahriyan Filibriza; Ainur Rovi Atur Rohmah; Anggun Sadiya Aurellia Ghani; Rofiq Hidayat (Litera Academica Publishing, 2025)
This study is motivated by the important role of school public relations in establishing effective communication between the school and parents, especially in strengthening the character of students at madrasah aliyah. The urgency of this research arises from challenges posed by the digital era and globalization, which have caused moral decline and character crises among adolescents. Therefore, collaboration between the school and parents becomes a crucial strategy to reinforce values such as religiosity, discipline, responsibility, and integrity in students. This study aims to analyze the management of school public relations in building harmonious and productive relationships with parents, as well as to examine the implementation of collaboration in supporting character education programs at madrasah aliyah. The research uses a qualitative approach with a field research design. Informants were selected purposively and include the head of the madrasah, teachers, public relations staff, and representatives of students' parents. Data collection was done through direct observation, in-depth interviews, and documentation, followed by descriptive analysis consisting of data reduction, data presentation, and conclusion drawing. The findings show that public relations management at madrasah aliyah plays a strategic role as the key liaison in designing, organizing, and implementing collaborative programs with parents. This collaboration involves intensive communication through parent forums, parenting programs, character reinforcement based on religious activities, and joint supervision of student behavior at home and school. The collaboration has a positive impact on character formation, seen in increased discipline, social concern, and responsibility among students. Thus, this study confirms that strengthening students' character depends not only on the school but also requires active parental involvement through effective public relations management.